Nostalgie et posthistoire dans quelques utopies louis-quatorziennes (1675-1714) - Peter Murvai (Conserveries Mémorielles)
The analysis the utopian texts published at the time of Louis XIV by Gabriel de Foigny, Denis Veiras and Tyssot de Patot demonstrates that they are dominated by a certain form of nostalgia that brings together references to an imaginary Antiquity and the New World in order to build imaginary republics that transcend History. Thus, inside this paradigm, the hypothesis of a correlation between the classical narrative utopias and the ideology of progress doesn’t stand scrutiny given the fact that these texts reject the foundations of liberalism in the name of the old ideal of the civic republicanism and of the simplicity of the Native Americans.